SIMULATION OF BIOMASS CARBONIZATION AND HEAT RECOVERY FOR ELECTRICITY PRODUCTION USING SEEBECK MODULES (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
This paper experimentally and numerically examines biomass carbonization and using thermoelectric modules to recover heat and generate electricity using the finite element method (FEM). Carbonization, conducted at high temperatures, produces charcoal and gases. The study identifies optimal temperatures for module placement, demonstrating that they can generate up to 6.5 W of electricity. Moreover, integrating the chimney to optimize the carbonization process produced hot air with a maximum gain of 11 °C above the ambient temperature. This approach enhances energy efficiency and reduces costs
Keywords: Pyrolysis; Wood biomass; Seebeck effect; Finite element method (FEM); Numerical simulation